The Great Gamble : The Soviet War in Afghanistan - Feifer, Gregory (GHQ, Rawalpindi Services Book Club, 2010)
The Soviet war in Afghanistan was a grueling debacle that has striking lessons for the 21st century. Parallels between the Soviet invasion of Afghanistan and the U.S. invasions of Afghanistan and Iraq are impossible to ignore. The Soviet Union sent some of its most elite troops to unfamiliar lands to fight a vaguely defined enemy, which eventually defeated their superior numbers with unconventional tactics.
Include Illustration Index
Keywords: The Great Gamble : the Soviet War in Afghanistan -- History -- Afghanistan -- Soviet Union